Social Media Impact on Oral Health Behavior Changes - Abdualkarim , Farouk; Al-Ghazaly, Yasin; Bramantoro, Taufan; Ramadhani, Nastiti Faradilla (International Journal of Psychosocial Rehabilitation, 2020)
Social media are part of people’s lifetime today as everybody is getting more addicted to them. They extremely affect the general health and health of the mouth and teeth. They are considered as a rich source of knowledge regarding the oral health as everyone can join famous groups that include professional experts in the oral health. Thus, the success depends on many factors until the right message arrives in the right way and there is no loss of time without benefit or addiction to the internet. The most notable social media at the current time are Facebook, WhatsApp, YouTube and Twitter, but the most used, influencing and popular platform is Facebook. This article outlines a background of social media websites, the historical review and advantages and disadvantages of social media using in the oral and dental health behaviours.